Subsequent Measurement for Investment Property: Fair Value Model - Rinelisa Prabandari, Ayu; Kholilah, Kholilah (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This study examines the effect of firm size, leverage, gain from revaluation, and information asymmetry on the possibility of choosing a fair value method of investment property moderated by institutional ownership. Methodology/approach: The quantitative research method with logistic and moderated regression analysis. The number of samples in this study was 117 companies. The final observation data during the 2018-2022 period was 585 firm years. Findings: The study's results proved that firm size and gain from revaluation affect the selection of the fair value method of investment property. In comparison, leverage and information asymmetry do not affect the selection of fair-value methods of investment property. In addition, institutional ownership can only moderate the effect of information asymmetry on selecting fair-value methods of investment property. Practical implications: The small number of companies that do not yet use fair value to measure investment properties can be used as material for consideration by the Financial Accounting Standards Drafting Board to improve regulations related to the use of fair value of investment properties. Companies can take this into account when choosing the best approach to ensure that financial statement readers can utilize them as a foundation for decision-making.   Originality/value: Adding the gain from revaluation as opportunistic motivation as the independent variable and institutional ownership as moderation variables.